Islamic Religious Education Learning Experiences and Muslim Students’ Beliefs and Practices in Eastern Ugandan Secondary Schools - Nimulola, Maimuna Aminah; Akbar, Halima Wakabi (Universitas Muhammadiyah Yogyakarta, 2024)
This study sought to determine the influence of IRE learning experiences on Muslim students’ beliefs and practices. The population consisted of Senior Four and Six students from Eastern Uganda from which a sample of 890 was selected using multi-stage sampling. A questionnaire was used to collect data, which was analyzed using descriptive statistics, correlation and ANOVA. The relationship between students’ learning experiences and their beliefs was found not to be statistically significant, while that between learning experiences and their practices was statistically significant and moderate. A statistically significant difference in students’ practices among school types was also found, where students from Government Non-Muslim schools had the lowest while those from Private Islamic schools had the highest. It was concluded that different types of schools offer different IRE learning experiences which influence ways in which Islam is practiced by students, although these experiences were not that influential on students’ beliefs. It therefore is recommended that Islamic extra-curricular activities be organized for students to boost their knowledge and skills.